2015
DOI: 10.1111/bcpt.12379
|View full text |Cite
|
Sign up to set email alerts
|

A Gelatinases‐targeting scFv‐based Fusion Protein Shows Enhanced Antitumour Activity with Endostar against Hepatoma

Abstract: Gelatinases play important roles in tumour invasion and metastasis and are thus considered promising targets for cancer therapy. In this study, a new single-chain variable fragment (scFv)-based fusion protein Fv-LDP, composed of the anti-gelatinases scFv and lidamycin apoprotein (LDP), was prepared, and its combination with angiogenesis inhibitor Endostar was then investigated. The fusion protein Fv-LDP specifically bound to various tumour cells, and its binding capability to human pulmonary giant cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The inhibition of these molecules could result in the suppression of these tumor development processes. Gao et al developed an anti-gelatinase scFv fused with the apoprotein, lidamidine (LDP), that when combined with Endostar, an angiogenesis inhibitor, curbed tumor growth in a xenotransplant murine model of human hepatoma [ 154 ].…”
Section: Applications Of Scfvsmentioning
confidence: 99%
“…The inhibition of these molecules could result in the suppression of these tumor development processes. Gao et al developed an anti-gelatinase scFv fused with the apoprotein, lidamidine (LDP), that when combined with Endostar, an angiogenesis inhibitor, curbed tumor growth in a xenotransplant murine model of human hepatoma [ 154 ].…”
Section: Applications Of Scfvsmentioning
confidence: 99%
“…Researchers also found that ES had an inhibitory effect on the invasion of human breast cancer cells by downregulating the expressions of MMP2 and MMP9 [18]. In other tumor fields, Gao et al [19] discovered that ES could enhance the anti-tumor activity of fusion protein in liver cancer. Thus, these studies further confirmed the role of ES in inhibiting metastasis of malignant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-drug conjugates already show its efficacy in cancer therapy in clinic, there are more than two antibody-drug conjugates already approved by US FDA until now. To improve the antitumor efficacy of lidamycin, antibody conjugated of lidamycin seems to be a reasonable approach to further improve the efficacy of lidamycin whereas lower the side effects after systemic intravenous injection, it was documented that antibody or its fragments conjugated with lidamycin showed improved antitumor efficacy as compared to lidamycin alone 3 - 5 .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that gelatianses were related with the prognosis and microvessel density (MVD) in patients with pancreatic cancer, and would be a potential target for cancer therapy 6 , 7 . Antibody against gelatinases had been developed and the conjugation of scFv against gelatinases with lidamycin already showed potent antitumor efficacy in several kinds of cancer types, such as lung cancer, hepatoma 5 , 8 , 9 . In this study, the antitumor efficacy of scFv-based fusion protein against gelatianses conjugated with lidamycin was investigated in pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%